Isolasi dan Identifikasi Cendawan Endofit Akar Anggrek Epifit Vanda sp. dan Anggrek Terestrial Spathoglottis plicata: Isolation and Identification of Root Endophytic Fungi in Epiphytic orchid Vanda sp. and Terrestrial Orchid Spathoglottis plicata - Rahayu, Nadiya Dwi; Sukarno, Nampiah; Listiyowati, Sri; Rafi, Mohamad; Sandra, Edhi; Mursidawati, Sofi; Risna (Jurnal Sumberdaya Hayati, 2024)
Endophytic fungi play an important role in the orchid lifecycle by aiding seed germination and plant development. Information on the diversity of endophytic fungi in Indonesian orchids, particularly Vanda epiphytic orchid and Spathoglottis terrestrial orchid, is still limited. This study aimed to isolate and identify endophytic fungi from the roots of Vanda sp. and Spathoglottis plicata orchids collected from Banjarbaru, South Kalimantan, and Kendari, Southeast Sulawesi. Isolation was performed using Potato Sucrose Agar (PSA) medium, and morphological identification was carried out through macroscopic and microscopic observations. A total of four endophytic fungal isolates were identified, including Nigrospora sp. and Penicillium sp. from Vanda sp. roots, and two isolates of Fusarium sp. from Spathoglottis plicata roots. The four fungal isolates obtained had aerial mycelium and septate hyphae, as well as conidia with diverse shapes. The diversity of endophytic fungi in orchid species could be influenced by the fungal affinity on the specific microhabitat conditions of each tissue and host plant species.